The Effect of Hermetia illucens larvae Formulation as Immunostimulant on Non-Specific Immune Response of Cyprinus carpio Challenged by Aeromonas salmonicida - Mauludia, Farida; Maftuch, Maftuch; Nurin, Febi Nadhila; Sebastian, Andhang (Research Journal of Life Science, 2021)
Cyprinus carpio is one type of freshwater fish. In Indonesia, carp outbreaks in carp since June 2002 have raised concerns, especially for fish farmers. One of the factors causing the outbreak of this disease is the bacteria Aeromonas salmonicida, which can cause fish to get sick and even die. Immunostimulants with natural ingredients that are environmentally friendly and can be used to increase the immune response of fish, one of which is maggot. The data analysis used in this study was a simple completely randomized design (CRD) with 6 treatments difference in the dose of maggot as an immunostimulant (0%, 25%, 50%, 75%, 100%) and three replications. The independent variable is the difference in the dose of maggot as an immunostimulant. The dependent variables include survival rate, total leucocytes, differential leukocytes, and water quality (pH, temperature, and DO). The FT-IR test results obtained that the best compound content in maggot flour is flavonoid compounds where these compounds can increase immune response. So, it is proven by phytochemical tests with positive maggot flour containing flavonoids, tannins, and alkaloids. In total erythrocytes, hematocrit, hemoglobin, total leukocytes, and differential leukocytes showed the best immune response in treatment C with a dose of 75% maggot.